Endovascular management of a large retroperitoneal haemorrhage resulting from dual testicular and intra-renal arterial injury after renal biopsy - Ahmed, Munawwar; Keshava, Shyamkumar Nidugala; Moses, Vinu; Valson, Anna T (Indian Journal of Radiology and Imaging, 2018)
Percutaneous renal biopsy is a minimally invasive procedure in the work up of a chronic kidney disease patient. However, it is not free from the complications. Hematuria and abdominal haemorrhage due to intra-renal artery injury are the common complications. We report and discuss the management of a rare case of retroperitoneal haemorrhage resulting from dual arterial injury involving left testicular artery and intra-renal artery.
Keywords: Computed tomography angiography; embolisation; hematuria